A diversidade cultural no direito internacional: a contribuição da convenção sobre a proteção e promoção da diversidade das expressões culturais para a mudança de paradigma no conceito internacional de direito cultural - Antonioli, Felipe (2023)
The objective of the study carried out is to identify whether the Convention on the Protection and Promotion of the Diversity of Cultural Expressions (2005) represented a break paradigm in the international concept of cultural diversity. To check the general objective, there are three specific objectives, namely: establishing how cultural diversity was treated before the Convention, analyzing its precedents within the World Trade Organization (WTO) and within the United Nations Educational, Scientific and Cultural Organization (Unesco); analyze how the creation occurred and the elements contemplated in the Convention of UNESCO on cultural diversity; identify whether a new dualistic concept of cultural diversity and some of its influences economic and socio-political. The objective of the study carried out is to identify whether the Convention on the Protection and Promotion of the Diversity of Cultural Expressions (2005) represented a break paradigm in the international concept of cultural diversity. To check the general objective, there are three specific objectives, namely: establishing how cultural diversity was treated before the Convention, analyzing its precedents within the World Trade Organization (WTO) and within the United Nations Educational, Scientific and Cultural Organization (Unesco); analyze how the creation occurred and the elements contemplated in the Convention of UNESCO on cultural diversity; identify whether a new dualistic concept of cultural diversity and some of its influences economic and socio-political.